Steps Taken for Development of Home Stay Tourism in Nepal - Adhikari, Bam Bahadur (NUTA Journal, 2020)
Home stay tourism which had formally started in 1988 in form of different variety and services, is still  in operation in many countries of today's world in different forms and is being operated as an important campaign to bring economic and social transformations. Home stay is being utilized as a business sector to make investments and generate income in developed countries whereas it is emphasized as a platform for production of local goods and generating employment in developing countries. Developed countries have been making huge investments in home stay and see it as a platform for business and entertainment, whereas it is being operated in different manner in developing countries. In developed countries like America, Europe, Australia, Canada etc, home stay is taken as a tool for earning high income. Developed countries emphasize on internal facilities which add to the attraction of outer environment while identifying the tourists' nature and objective and provide similar facilities. They provide required facilities for food, accommodation, studying, playing, yoga, capacity building and providing training to draw the attention of tourists. The responsibility has come upon the shoulders of related representative organizations and tourism professionals to develop home stay business as a sustainable, good quality and target based tourism. In this context, Nepalese government should develop the concept of home stay tourism in planned manner and identify its vast possibilities. It is important to have the proper direction and helpful role from the government of Nepal in home stay tourism sector which has been developing in rural areas of Nepal, along with the proper management rules and guidelines from the government's side. This article focuses in the business related to home stay and prioritizes the promotional, managerial and developmental aspects of this tourism business in Nepal.